Genetic variability for seed yield and other quantitative characters in cowpea - Araújo, João Pratagil Pereira de; Nunes, Raimundo de Pontes (Pesquisa Agropecuaria Brasileira, 2014)
Genetic and phenotypic components of variance as well as heritability, expected genetic advances and genetic coefficient of variability were estimated for five cowpea cultivars (Vigna unguiculata (L) Walp.) for several morphological characters, seed yield and some yield components. The estimated genetic parameters were very low for seeds per pod and for vegetative characteristics like nodes on the main stem, number of branches, stem diameter and number of leaves suggesting genetic uniformity for the studied cultivars and little chance of genetic advance through selection breeding methods for these characters. Leaf area and pod length gave high estimated values. Among the yield components, only number of seeds per pod presented low values for the parameters studied. For number of pods per plant, 100-seed weight, and yield, high estimated values were obtained. Hence it is theoretically expected that selection would result in good genetic improvement for these caracters.